A Critique of Theories and Theorizing in Social Sciences: Special Reference to Islamic Political Experience (American Journal of Islam and Society, 2001)
This paper seeks to present a critique of and an alternative to theoriesand theorizing employed by social scientists to explain the relationshipbetween religion and politics in general and Islamic PoliticalExperience in particular. Within the context of the paper we argued thatpolitcal theory can be conveniently understood in terms of theco-existence of two distinct and rival styles of though Positivism andhistoricism. For the lack of better terms we take positivism andhistoricism to be conventional and radical paradigms respectively. Theparadigms are found wanting in that they do not have the capacity toprovide a satisfactory framework of ideas and common vocabularlywith which to conduct discourse on Islamic Political Experience. In anycase, for a paradigm to do that, it must become fully subsumed in anIslamic worldview. A paradigm presented as a critique and alternativeto these paradigms is based on conceptual analysis, with pure Qur’anicand Shariah concepts providing both the framework and methdologicaltools of analysis. It is an axiomatic approach as it involves systematicanalysis of a number of axioms, the starting point of which is the ideaof the totality of Islam as an ideal which Muslims endeaovur toconcretize.